Let
n = 0 ∑ ∞ ( 2 n + 5 ) ! ( 2 n ) ! = A ln 2 + B
where A and B are rational numbers. Find A + B 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S = n = 0 ∑ ∞ ( 2 n + 5 ) ! ( 2 n ) !
S = n = 0 ∑ ∞ ( 2 n ) ! ⋅ ( 2 n + 1 ) ( 2 n + 2 ) ( 2 n + 3 ) ( 2 n + 4 ) ( 2 n + 5 ) ( 2 n ) !
S = n = 0 ∑ ∞ ( 2 n + 1 ) ( 2 n + 2 ) ( 2 n + 3 ) ( 2 n + 4 ) ( 2 n + 5 ) 1
By partial fractions:
S = 2 4 1 ⎣ ⎡ n = 0 ∑ ∞ 2 n + 1 1 − 2 n + 2 4 + n = 0 ∑ ∞ 2 n + 3 6 − 2 n + 4 4 + n = 0 ∑ ∞ 2 n + 5 1 ⎦ ⎤
On second sum, make k = n + 1 . On third sum, make l = n + 2 :
S = 2 4 1 ⎣ ⎡ n = 0 ∑ ∞ 2 n + 1 1 − 2 n + 2 4 + k = 1 ∑ ∞ 2 k + 1 6 − 2 k + 2 4 + l = 2 ∑ ∞ 2 l + 1 1 ⎦ ⎤
Taking off the first two terms of the first sum, the first term of the second sum, and standardizing the variable for all sums as n :
S = 2 4 1 ⎣ ⎡ 1 − 2 + 3 1 − 1 + n = 2 ∑ ∞ 2 n + 1 1 − 2 n + 2 4 + 2 − 1 + n = 2 ∑ ∞ 2 n + 1 6 − 2 n + 2 4 + n = 2 ∑ ∞ 2 n + 1 1 ⎦ ⎤
S = 2 4 1 ⎣ ⎡ − 3 2 + n = 2 ∑ ∞ 2 n + 1 8 − 2 n + 2 8 ⎦ ⎤
S = 2 4 1 ⎣ ⎡ − 3 2 + 8 n = 5 ∑ ∞ n ( − 1 ) n + 1 ⎦ ⎤
S = 2 4 1 ⎣ ⎡ − 3 2 + 8 ⎝ ⎛ n = 5 ∑ ∞ n ( − 1 ) n + 1 + 1 − 2 1 + 3 1 − 4 1 − 1 + 2 1 − 3 1 + 4 1 ⎠ ⎞ ⎦ ⎤
S = 2 4 1 ⎣ ⎡ − 3 2 + 8 ⎝ ⎛ n = 1 ∑ ∞ n ( − 1 ) n + 1 − 1 + 2 1 − 3 1 + 4 1 ⎠ ⎞ ⎦ ⎤
S = 2 4 1 ⎣ ⎡ − 3 2 + 8 ⎝ ⎛ n = 1 ∑ ∞ n ( − 1 ) n + 1 ⎠ ⎞ − 3 1 4 ⎦ ⎤
S = 2 4 1 ⎣ ⎡ 8 ⎝ ⎛ n = 1 ∑ ∞ n ( − 1 ) n + 1 ⎠ ⎞ − 3 1 6 ⎦ ⎤
S = 3 1 ⎝ ⎛ n = 1 ∑ ∞ n ( − 1 ) n + 1 ⎠ ⎞ − 9 2
From Maclaurin Series of ln ( 1 + x ) , ∣ x ∣ ≤ 1 , x = − 1 :
S = 3 1 ln ( 2 ) − 9 2
So:
A = 3 1 , B = − 9 2 → A + B 1 = 9
Problem Loading...
Note Loading...
Set Loading...
S = n = 0 ∑ ∞ ( 2 n + 5 ) ! ( 2 n ) ! = n = 0 ∑ ∞ ( 2 n + 1 ) ( 2 n + 2 ) ( 2 n + 3 ) ( 2 n + 4 ) ( 2 n + 5 ) 1 = 2 4 1 n = 0 ∑ ∞ ( 2 n + 1 1 − 2 n + 2 4 + 2 n + 3 6 − 2 n + 4 4 + 2 n + 5 1 ) By partial fraction decomposition
= 2 4 1 ( 1 1 − 2 4 + 3 6 − 4 4 + 5 1 + 3 1 − 4 4 + 5 6 − 6 4 + 7 1 + 5 1 − 6 4 + 7 6 − 8 4 + 9 1 + ⋯ ) = 2 4 1 ( 1 1 − 2 4 + 3 7 − 4 8 + 5 8 − 6 8 + 7 8 − 8 8 + 9 8 − ⋯ ) = 2 4 1 ( 1 8 − 2 8 + 3 8 − 4 8 + 5 8 − 6 8 + 7 8 − 8 8 + 9 8 − ⋯ ) − 2 4 1 ( 1 7 − 2 4 + 3 1 ) = 3 1 ln 2 − 9 2
Therefore A + B 1 = 3 1 − 9 2 1 = 9 .